SISTEM INFORMASI MANAJEMEN MLIJO BERBASIS WEBSITE DAN MOBILE - Fery Febbyanto; Irwan Alnarus Kautsar; Uce Indahyanti (Jurnal Tekinkom (Teknik Informasi dan Komputer), 2023)
The term "Bakul Mlijo" is used by the people in Mojokerto to refer to itinerant vegetable traders because they generally use carts or baskets (baskets) as a place to put their wares. The term "Mlijo" probably comes from the Javanese language which means "profit". Mobile vegetable traders are a retail business that is included in the non-store retailer category (direct selling) which sells basic necessities such as vegetables, fruits and fish which are sold directly to the end consumer. The main purpose of development research is the development of new products or innovations and their effectiveness in achieving the goals set. Therefore, the R&D method is a very useful research method in product or tool development, including in tool design research and tool testing as described in the question. Bakul Mlijo uses information system technology for customer satisfaction. Mlijo customers shop easily and without much time and can make purchases using payment methods. This system can facilitate mlijo operations such as answering questions about prices and so on, because all information related to goods has been prepared in the mlijo application. This research contributes to the development of services to customers and facilitates the marketing of Bakul Mlijo merchandise.